Interpretations of Food in French Sociology of Imaginary - Grassi, Valentina (Italian Sociological Review, 2013)
Sociology of imaginary in French context was born thanks to the recovery of the theories of the anthropologist Gilbert Durand for the study of social phenomena by Michel Maffesoli. Concerning the food, the analysis of the imaginary regimes by Durand places the archetype of nourishment within the mystical structures of imagination. It’s possible, through alimentary practices, to discover the cultural axes of a society and its imaginary. According to Maffesoli, eating together is a social act of communion, it is a communication process and a relational exchange. Nowadays, postmodern imaginary is making its way toward a new ecological alimentary wisdom, which Maffesoli calls eco-sophia.